Influence of halal credence, halal awareness, halal certification, and health consciousness to halal purchase intention through STHF (Satisfaction towards halal food) and religiosity as a moderation variable - Fernando, Fernando; Dewi, Citra Kusuma (Edelweiss Applied Science and Technology, 2025)
Consumer interest in halal goods continues to increase, along with increasing public awareness of halal aspects of food consumption. This research analyzes the influence of "Halal Credence, Halal Awareness, Halal Certification, and Health Consciousness on Satisfaction Towards Halal Food (STHF)." A quantitative methodology was utilized in this research. This research uses primary data sources, such as online questionnaires via Google Forms and PLS-SEM analysis techniques. This research shows that Halal Credence, Halal Awareness, Halal Certification, and Health Consciousness positively affect satisfaction with halal food (STHF). Furthermore, STHF positively affects the intention to purchase halal products (Halal Purchase Intention) and acts as a mediating variable in the relationship between these factors and the intention to purchase halal. Moreover, Religiosity acts as a moderating variable, which strengthens the relationship between STHF and Halal Purchase Intention, indicating that the higher a person’s Religiosity, the stronger the influence of satisfaction with halal food on halal purchase intention. This finding also has practical implications for MSME meat shops in Bandung, suggesting they should enhance halal certification visibility, highlight health benefits, engage religious consumers, and maintain high-quality standards to increase satisfaction and boost sales of halal products.